ON SOME SELECTED PROBLEMS OF KOREAN ABBREVIOLOGY - BOROWIAK, Anna (International Journal of Korean Humanities and Social Sciences, 2016)
Given the fact that we live in the era where the pace of life is constantly speeding up, it is no surprise that ‘the economy of language’ - meaning the efficient usage of language in order to achieve the maximum effect for the minimum effort has become so important in everyday life. Using abbreviated forms of different kinds is supposed to help us to economize continuously insufficient amount of time. Their overuse, however, can hamper effective communication and bring the adverse effect from what the speaker’s intention was – namely to communicate the message clearly and unambiguously and receive a response to it in a short time. Incomprehension or misunderstanding of the message leads, in fact, to unnecessarily prolonging the conversation since it requires asking additional questions in order to explain what is unclear to the listener. Reduced forms used mainly in spoken Korean can largely be divided into lexical and grammatical ones. Lexical shortenings of different kinds such as acronyms, blends, clippings etc. although rarely and rather briefly discussed by Korean linguists and basically excluded from the debate on word-formation issues definitely deserve much more attention taking into account their extensive usage. As for grammatical abbreviations, despite its frequent occurrence, the subject is not that often taken up and discussed either. The aim of this article is to present some characteristic properties of grammatical abbreviations used mainly in spoken Korean. The reduced forms in question will be divided into three categories namely - particles, endings and grammatical constructions and discussed separately. This article however focuses only on those abbreviated forms, which means leaving the subject of particle or word ellipsis beyond its scope.